At the interface between language testing and second language acquisition: Language ability and context of learning. (January 2014) - Gu, Lin
This study investigated the relationship between latent components of academic English language ability and test takers' study-abroad and classroom learning experiences through a structural equation modeling approach in the context of TOEFL iBT ® testing. Data from the TOEFL iBT public dataset were used. The results showed that test takers' performance on the test's four skill sections, namely listening, reading, writing, and speaking, could be accounted for by two correlated latent components: the ability to listen, read, and write, and the ability to speak English. This two-factor model held equivalently across two groups of test takers, with one group having been exposed to an English-speaking environment and the other without such experience. Imposing a mean structure on the factor model led to the finding that the groups did not differ in terms of their standings on the factor means. The relationship between learning contexts and the latent ability components was further examined in structural regression models. The results of this study suggested an alternative characterization of the ability construct of the TOEFL test-taking population, and supported the comparability of the language ability developed in the home-country and the study-abroad groups. The results also shed light on the impact of studying abroad and home-country learning on language ability development.